2020
DOI: 10.26760/terracotta.v2i1.4289
|View full text |Cite
|
Sign up to set email alerts
|

Fasilitas Ruang Khusus Pada Sekolah Inklusi Binar Indonesia (Bindo) di Bandung

Abstract: ABSTRAK     Diterbitkannya Rencana Induk Pengembangan Pendidikan Inklusif Tingkat Nasional Tahun 2019 – 2024, memperkuat keinginan pemerintah dalam membuat konsep sekolah pendidikan inklusi. Sekolah Inklusi merupakan sebuah pelayanan pendidikan dimana Anak Berkebutuhan Khusus (ABK) belajar bersama satu ruang dengan anak normal. Mereka belajar bersama, meskipun kemungkinan materi yang diberikan berbeda. Saat ini belum ada standar fasilitas kebutuhan ruang untuk sekolah inklusi. Penelitian ini menganalisa kebutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Abdullah's research (2020) shows a positive and significant influence between the education management information system and the social competence of teachers together on parental satisfaction. Utami and Putra (2020) also found that the availability of special services such as special rooms for CSN, including study rooms, meditation rooms, and parent consultation rooms, are closely related to parental satisfaction with inclusive education services. The results of these studies indicate that it is important for educational institutions to develop services that are oriented towards the satisfaction of parents as parties who are also interested in providing the best education rights for their children; especially for CSN by providing additional accompanying teachers who have skills in accordance with CSN.…”
Section: Introductionmentioning
confidence: 89%
“…Abdullah's research (2020) shows a positive and significant influence between the education management information system and the social competence of teachers together on parental satisfaction. Utami and Putra (2020) also found that the availability of special services such as special rooms for CSN, including study rooms, meditation rooms, and parent consultation rooms, are closely related to parental satisfaction with inclusive education services. The results of these studies indicate that it is important for educational institutions to develop services that are oriented towards the satisfaction of parents as parties who are also interested in providing the best education rights for their children; especially for CSN by providing additional accompanying teachers who have skills in accordance with CSN.…”
Section: Introductionmentioning
confidence: 89%